The Effect Analysis of Reservoir Height Variations at the Pico-Hydro System to Charger a Laptop Battery - Syamsuri, Syamsuri; Maulana, Hasan Syafik; Kusuma, Wendy Candra (TURBO [Tulisan Riset Berbasis Online], 2019)
Energy has become a very serious problem in many countries, one of which is electric energy. Water is the latest energy that deserves to be developed and also utilized to the fullest. In addition to the source of our life, water is also an energy that can be utilized for a variety of things including the development of technology, such as the energy source for hydroelectric power generation such as pico hydro. An example of piko-hydro is a Pelton turbine that utilizes the flow of water from a height.  Among other advantages, the power produced is large, simple construction, easy to maintain, the technology that is simple and easy to apply in isolated areas.  In generating the maximum electric energy, research is conducted experimental studies of the influence of Pelton turbine head height variation of the electrical energy that is generated to turn on the laptop.  The study was carried out in the ITATS H building using a variety of valve openings and head heights of 18º, 36º, 54º, 72º, 90º and 17, 12.5, and  9  meters on Pelton turbines.  Based on research and data analysis, the greatest electrical power is obtained, which is 3.96 Watts at variations of the valve opening 90º and with a reservoir height of 17 meters. The maximum efficiency system achieved at the water reservoir height of the 17 meters with 90 valve openings is 14.56%. The results of the electrical power produced by this Pelton turbine can be used to charge the laptop for 2.18 hours